A survey investigating the current practice of French health professionals regarding infection risk after monkey bites. (12th December 2019) - Gauthier, Pauline; Bellanger, Anne‐Pauline; Bozon, Fabienne; Lepiller, Quentin; Chirouze, Catherine; Marguet, Philippe
Abstract: International tourism is steadily increasing, with 15% of travellers reporting health problems when they come back. Animal bites represent 2% of consulting causes, of which 20% are due to monkey bites. The Monkey B virus ( Macacine alphaherpesvirus 1) is an alphaherpesvirus ( Herpesviridae, genus Simplexvirus ) enzootic in macaques (Genus Macaca ). Zoonotic infections with the Monkey B virus following exposure to macaques are exceptionally rare, but can cause fatal encephalomyelitis in humans. An observational survey was undertaken in 2018 to assess the practice of French health professionals regarding infection risk after monkey bites. French health professionals practicing in vaccination and rabies centres were specifically targeted for this study. Standardized questionnaires were sent by email to a sample of French health professionals. They were asked to participate on a voluntary and anonymous basis. The questionnaires requested epidemiological details and included multiple‐choice questions about the infection management of monkey bites. The response rate was 33.5%. The frequency of monkey bites in 2017 was variable with a minority of centres managing more than 6 per year (12%), 46% managing 1–5 monkey bites and 42% none. Most of the monkey bites were described as occurring in South Asia at tourist sites, on naked upper limbs, shortly after the travellers arrived at their destination. Tetanus status verification, rabies post‐exposure prophylaxis and antibiotic therapy were said to be prescribed in most cases. Knowledge about the Monkey B virus was reported as scarce for 38% of the participants. The number of monkey bites managed per year per centre varied greatly but practices regarding infectious risk after monkey bites were generally homogeneous. The risk of Monkey B virus transmission did not readily come to mind in the differential diagnosis of infection risk for many French health professionals.